2020
DOI: 10.1371/journal.pone.0233811
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum interleukin-6 and soluble interleukin-2-receptor levels with disease activity status in patients with inflammatory bowel disease: A prospective observational study

Abstract: Crohn's disease (CD) and ulcerative colitis (UC) are characterized by overexpression of proinflammatory cytokines. We determined the association of serum levels of interleukin (IL)-6, soluble-IL-2-receptor (sIL-2R) and CRP as well as of faecal calprotectin (FC) values with disease activity in CD and UC patients. This prospective study included 145 CD and 84 UC patients. Serum proinflammatory biomarkers and FC levels were measured and demographic, clinical and endoscopic characteristics were collected. Uni-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…We found serum IL-6 significantly higher in CD patients with active than inactive disease ( Table I ). The ratio of median serum IL-6 in active and inactive CD of 2.12 was similar to that reported by Mavropoulou et al [ 25 ], but lower than in a study by Nikolaus et al [ 24 ]. Diagnostic performance of IL-6 in differentiating active and inactive disease was in our study worse than that of CRP ( Table II ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found serum IL-6 significantly higher in CD patients with active than inactive disease ( Table I ). The ratio of median serum IL-6 in active and inactive CD of 2.12 was similar to that reported by Mavropoulou et al [ 25 ], but lower than in a study by Nikolaus et al [ 24 ]. Diagnostic performance of IL-6 in differentiating active and inactive disease was in our study worse than that of CRP ( Table II ).…”
Section: Discussionsupporting
confidence: 88%
“…IL-6 is also a candidate marker for CD course and treatment monitoring. It was demonstrated to be associated with disease activity [ 22 25 ], to predict endoscopic IBD activity in combination with serum amyloid A (SAA), IL-8, and eotaxin-1 [ 26 ], and to predict the response to biologic treatment in CD patients [ 27 , 28 ]. However, there are also reports that do not confirm the diagnostic utility of IL-6 in CD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the level of sIL-2R is elevated during the acute or aggravated phase of the disease and decreased during the convalescence period or after treatment [24,25]. Park found [26,27] In this study, sIL-2R was found to be significantly increased in patients with poor outcomes in COPD exacerbation, suggesting that sIL-2R may play a potential role in COPD exacerbation.…”
Section: Discussionsupporting
confidence: 49%
“…Cytokines, such as IL-6 and soluble IL-2 receptor (sIL-2R), have been shown to modulate the intestinal immune system. Mavropoulou et al [ 44 ] analyzed serum IL-6 and sIL-2R levels in a cohort of IBD patients. They evaluated the correlation between these laboratory markers and clinical and endoscopic disease activity status in IBD patients.…”
Section: Resultsmentioning
confidence: 99%